The Influence of Work Environment, Job Promotion and Work Motivation on the Functional Performance of Tax Auditors at the Tax Service Office at the Bali Regional Tax Office - Ardian Galih Prastowo; Kadek Rai Suwena; Ni Made Suci (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The capacity of public sector organizations to deliver effective services depends significantly on how well their employees perform. In the context of tax auditing, both organizational and individual factors are thought to shape the level of performance employees ultimately achieve. This study centers on the functional performance of Tax Auditors at the Regional Office of the Directorate General of Taxation in Bali, examining how work environment, job promotion, and work motivation relate to and influence that performance. A total of 90 respondents were selected through proportionate random sampling, with data gathered directly via structured questionnaires distributed to each participant. The collected data were analyzed using multiple linear regression to determine the extent to which each independent variable meaningfully affects employee performance. The findings confirm that work motivation has a statistically significant and substantive effect on driving performance improvements among employees. Work environment and job promotion, by contrast, did not individually demonstrate a direct and significant effect on performance; however, when all three variables were tested simultaneously, they collectively accounted for a substantial portion of the variation in employee performance across the sample. These results suggest that efforts to boost employee performance should concentrate primarily on strengthening intrinsic motivation at the individual level, while also being supported by an organizational climate that is conducive to sustained encouragement and growth.